Epidomological and clinico -therapeutic studies on canine demodicosis - Thushara M R (Department of Veterinary Epidemiology and Preventive Medicine, College of Veterinary and Animal Sciences, 2003)
Prevalence of demodicosis was studied among the dogs presented with dermatological problems at the University Veterinary Hospitals, Mannuthy and Kokkalai during the period from May 2002 to April 2003. Among the 927 dermatological problems in canines, demodicosis was diagnosed in 51 (5.50 per cent) and scabies (Sarcoptes scabei var canis) in three (0.03 per cent) cases. Significant difference (P<0.05) in the proportion of positive cases was noted among different age groups of dogs with the highest rate of infection in 6 to 12 months age group followed by three to six months. Highest rate of infection was observed in Boxers followed by Golden retrievers and Rotteweilers and lowest in Dachshunds, the difference being statistically significant (P<0.05). No influence of sex was observed on the prevalence of demodicosis. Papules and pustules were the most frequent primary lesions and erythema and alopecia, the predominant secondary lesions distributed mostly on the face, neck and extremities with occasional lesions on the trunk of the affected dogs. Constant pruritus with diffuse pattern of alopecia was observed in most of the generalised demodicosis while the pruritus was absent or occasional and rarely constant in localised demodic;sis. Out of six incontact animals affected, four were from the same litter indicating the transmission of the disease from the mother to neonate at the time of suckling. Dogs kept outdoors were less frequently affected. A significant reduction in the haemoglobin, PCV and albumin globulin ratio and an elevation in absolute eosinophil count and globulin content (P<0.05) was observed in the affected dogs. All the treatments were effective in bringing these values towards their normal level in the control group.